Calculation of surface potentials at the silica–water interface using molecular dynamics: Challenges and opportunities. (27th February 2018) - Lowe, Benjamin M.; Skylaris, Chris-Kriton; Green, Nicolas G.; Shibuta, Yasushi; Sakata, Toshiya
Abstract: Continuum-based methods are important in calculating electrostatic properties of interfacial systems such as the electric field and surface potential but are incapable of providing sufficient insight into a range of fundamentally and technologically important phenomena which occur at atomistic length-scales. In this work a molecular dynamics methodology is presented for interfacial electric field and potential calculations. The silica–water interface was chosen as an example system, which is highly relevant for understanding the response of field-effect transistors sensors (FET sensors). Detailed validation work is presented, followed by the simulated surface charge/surface potential relationship. This showed good agreement with experiment at low surface charge density but at high surface charge density the results highlighted challenges presented by an atomistic definition of the surface potential. This methodology will be used to investigate the effect of surface morphology and biomolecule addition; both factors which are challenging using conventional continuum models.